NEDD4 single nucleotide polymorphism rs2271289 is associated with keloids in Chinese Han population - Zhao, Ying (Am J Transl Res, 2016)
Keloids are abnormally raised fibroproliferative lesions that usually occur following cutaneous traumas. Recently, a large-scale genome-wide association study (GWAS) has identified multiple single nucleotide polymorphisms (SNPs) in three genetic loci that are associated with keloids in Japanese population. Subsequently, two reported loci 1q41 (rs873549 and rs1442440) and 15q21.3 (rs2271289) for keloids were confirmed in selected Chinese population. The association of these SNPs with clinical features of keloids, has not yet been studied. To explore the role of these SNPs in the pathogenesis of keloids, we performed a case-controlled study in another independent Chinese Han population to analyze the correlation between 4 SNPs (rs873549, rs2118610, rs1511412, rs2271289) and keloids phenotypes. 309 keloids patients and 1080 control subjects were included. The results showed that, in the dominant mode of inheritance, the minor allele T of SNP rs2271289 had significantly higher odd ratios (ORs) in the severe keloid group compared with both the controls and the mild keloid group. The ORs were maintained after Bonferroni’s correction (OR: 4.09, 95% CI: 1.78-9.37, P-value 3.25E-04). The ratio of the severe: mild OR for rs2271289 (dominant model) is (4.73/1.84=2.57). Similar associations in SNP rs2271289 were seen for groups with no family history and multiplesite compared with the control groups. No associations between keloid number, family history or severity relative to the controls were observed for the other three SNPs. Our data support that rs2271289 is strongly associated with severe keloids and might contribute to the complexity of clinical features of keloids.